Interleukin-34-regulated T-cell responses in rheumatoid arthritis - Park, Hye Eun; Oh, Hanna; Baek, Jea-Hyun (Frontiers in Medicine, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease with a multifaceted etiology, which primarily affects and results in the deterioration of the synovium of patients. While the exact etiology of RA is still largely unknown, there is growing interest in the cytokine interleukin-34 (IL-34) as a driver or modulator of RA pathogenesis on the grounds that IL-34 is drastically increased in the serum and synovium of RA patients. Several studies have so far revealed the relationship between IL-34 levels and RA disease progression. Nevertheless, the significance and role of IL-34 in RA have remained ambiguous, as illustrated by two most recent studies, which reported contrasting effects of genetic IL-34 deletion in RA. Of note, IL-34 is a macrophage growth factor and is increasingly perceived as a master regulator of T cell responses in RA via macrophage-dependent as well as T cell-intrinsic mechanisms. In this regard, several studies have demonstrated that IL-34 potentiates helper T cell (Th) responses in RA, whereas studies also suggested that IL-34 alleviates synovial inflammation, potentially by inducing regulatory T cells (Treg). Herein, we provide an overview of the current understanding of IL-34 involvement in RA and outline IL-34-mediated mechanisms in regulating T-cell responses in RA.